STUDENTS’ ARGUMENTATION TEXT ANALYSIS IN INDONESIA USING APPRAISAL APPROACH (APPRECIATION) - Atika Lisamawati; Wahyu Rima Agustin; Dessy Dwijayanti (Acceleration: Multidisciplinary Research Journal, 2024)
This research is qualitative descriptive research with a fixed case study that has the following objectives: to describe students' opinions in the text about "Services in Private Hospitals are better than services in State Hospitals". Hence after, to determine and describe data expressions included in the appraisal category. Furthermore, to describe data expressions included in appraisal appreciation. The data in this study were obtained through document analysis and Focus Group Discussion (FGD). The instruments in this study were documentation and interviews. In the study, 444 data were found. The 403 data were included in the category of Appraisal assessment types: Appreciation-Valuation. The data obtained were divided into 2 types of assessments, 1) assessment of Private Hospital and State Hospital services, 2) assessment of Private Hospital and State Hospital facilities. From these findings, the average expression used by students to describe Private Hospital services was; quality and so on 20 data, professional 22 data, faster 12 data, fast 10 data, quality 20 data, friendly 8 data, more friendly 10 data, friendly 8 data, more friendly 10 data, efficient 22 data, great 13 data, good 19 data, and bad 1 data. Based on the study, it was found that there were shortcomings in the results of the argumentative text produced by students. When asked to write an argumentative text, students in giving their opinions were still not persuasive. There are fundamental differences that students must understand regarding the differences between opinion texts and argumentative texts, namely: the purpose of making the text.